Improving Children's Social Behavior Through Group Work Methods in Group B of Pertiwi Langko Kindergarten - Imelda, Imelda; Agusniatih, Andi; Nurhayati, Sri (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
The main problem underlying this research is the low social behavior of early childhood children, demonstrated by a tendency to be individualistic, reluctant to share, less willing to cooperate, dominate games, and minimal empathy and concern for friends. This condition emphasizes the importance of implementing learning methods that can encourage active involvement of children while honing their social skills. This research aims to improve children's social behavior by implementing group work methods. The research uses a qualitative descriptive approach with the type of Classroom Action Research (CAR). This was carried out in two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. The research subjects were early childhood group B consisting of 14 children. Data were obtained through observation, interviews, and documentation which were then processed through qualitative descriptive analysis supported by simple quantitative data. The research findings indicate an increase in children's social behavior, especially in the aspects of cooperation, sharing, and helping each other. In the pre-action stage, most children were in the underdeveloped category, while in the second cycle most children had reached the category of developing as expected to developing very well. The results of this study confirm that the group work method is effective in improving the social behavior of early childhood children. This research contributes to the development of collaborative learning strategies that focus on strengthening children's social-emotional aspects from an early age.